Anti-Positivisme Ronald Dworkin: Menalar Hukum sebagai Moralitas - Tanius Sebastian (Undang: Jurnal Hukum, 2023)
Ronald Dworkin was a contemporary American legal theorist whose ideas of the nature of law had strikingly compelled legal positivists to amend a number of their basic tenets. In this paper, Dworkin’s pivotal legacy on troika of jurisprudence, legal theory, and philosophy of law will be assessed, in the light of interpretive nature of legal practice undertaken by their officials or professionals. Thus, it will demonstrate three focal points of his legal thought, i.e. the idea of anti-positivism, legal reasoning as moral reasoning, and legal (in)determinacy. Those are exhibited in Dworkin’s final oeuvre, Justice for Hedgehogs, which refers to the notable Classical Greek metaphor made famous by Sir Isaih Berlin on the picture of law and morality: the fox and the hedgehog. Dworkin drew on this metaphor to accentuate his long-standing commitment on the unity of law and morality. Accordingly, this article will situate Dworkin in Indonesia jurisprudential problem in the context of legal pluralism. My primary intention is to examine the transposition of the Dworkinian concept of jurisprudence to the concept of Indonesian legal science. To that end, a comparative glance is inevitable, and it will make the case for several impediments to use Dworkin’s thoughts in the legal ambiguity and uncertainty in Indonesia. Abstrak Ronald Dworkin adalah seorang teoretikus hukum Amerika kontemporer dengan gagasan-gagasan yang memaksa para tokoh positivis hukum untuk mengamandemen beberapa corak dasar teorinya. Di dalam tulisan ini, warisan Dworkin yang paling penting mengenai ilmu, teori, dan filsafat hukum akan diulas berdasarkan hakikat interpretatif praktik hukum sebagaimana digeluti oleh para pengemban hukum profesional. Di sini akan diajukan tiga pokok pemikiran hukum Dworkin, yakni paham anti-positivisme, penalaran hukum sebagai penalaran moral, dan ke(tidak)pastian hukum. Kesemuanya itu tampak di dalam karya Dworkin yang terakhir, Justice for Hedgehogs, yang merujuk pada metafora Yunani Klasik tentang Sang Rubah dan Sang Landak yang diperkenalkan oleh Sir Isaiah Berlin. Dworkin menggunakan metafora ini untuk menegaskan komitmen lamanya tentang kesatuan hukum dan moralitas. Dalam pada itu, artikel ini akan mendudukkan Dworkin ke dalam masalah keilmuan hukum Indonesia dengan konteks pluralisme hukum. Maksud utamanya adalah untuk menyelidiki transposisi konsep filsafat hukum Dworkinian ke konsep ilmu hukum Indonesia. Untuk itu, telaah dengan sentuhan komparatif menjadi tak terhindarkan, dan dengannya hendak dinyatakan bahwa terdapat sejumlah tantangan dalam menggunakan pemikiran Dworkin di dalam ambiguitas dan ketidakpastian hukum di Indonesia.